Achnatherum pilosum (Stipeae, Poaceae), a new species from Qinghai-Tibet Plateau - Zhang, Zhong-Shuai; Jiang, Shan-Wen; Chen, Wen-Li (Phytotaxa, 2018)
A new species of Achnatherum from Qinghai-Tibet Plateau is described and illustrated. It is distinguished from other species of the genus by attributes of ligules, panicles, glumes, lemmas, awns and anthers. Evidence from lemma epidermal pattern, cytology and morphology confirm its systematic position in Achnatherum s.s.